Real- and momentum-indirect neutral and charged excitons in a multi-valley semiconductor - Huang Zhiheng; Li Yuhui; Bo Tao; Zhao Yanchong; Wu Fanfan; Li Lu; Yuan Yalong; Ji Yiru; Liu Le; Tian Jinpeng; Chu Yanbang; Zan Xiaozhou; et al. (National Science Open, 2023)
Excitons dominate the photonic and optoelectronic properties of a material. Although significant advancements exist in understanding various types of excitons, progress on excitons that are indirect in both real- and momentum-spaces is still limited. Here, we demonstrate the real- and momentum-indirect neutral and charged excitons (including their phonon replicas) in a multi-valley semiconductor of bilayer MoS2, by performing electric-field/doping-density dependent photoluminescence. Together with first-principles calculations, we uncover that the observed real- and momentum-indirect exciton involves electron/hole from K/Γ valley, solving the longstanding controversy of its momentum origin. Remarkably, the binding energy of real- and momentum-indirect charged exciton is extremely large (i.e., ~59 meV), more than twice that of real- and momentum-direct charged exciton (i.e., ~24 meV). The giant binding energy, along with the electrical tunability and long lifetime, endows real- and momentum-indirect excitons an emerging platform to study many-body physics and to illuminate developments in photonics and optoelectronics.